Angiographic characteristics associated with rupture of small intracranial aneurysms - Goertz, Lukas; Zopfs, David; Pennig, Lenhard; Jünger, Stephanie T.; Grunz, Jan-Peter; Timmer, Marco; Görtz, Magdalena; Huflage, Henner; Luetkens, Karsten Sebastian; Kabbasch, Christoph; Zaeske, Charlotte (World neurosurgery, 2023)
Objective - Contrary to previous assumptions, there is increasing evidence that small intracranial aneurysms carry a relevant risk of rupture. The aim of this study was to identify angiographic characteristics of small ruptured aneurysms ≤7 mm and to evaluate their significance for clinical decision making. - Methods - A total of 385 patients with 149 unruptured and 236 ruptured intracranial aneurysms were retrospectively compared. Two- and three-dimensional digital subtraction angiography was used to determine aneurysm location, various size parameters, angulations, and morphology, as well as parent artery diameter. - Results - Aneurysms of the anterior communicating artery, the posterior inferior cerebellar artery, and the internal carotid artery terminus had a significantly increased prevalence among ruptured aneurysms. Ruptured aneurysms were characterized by a significantly larger aneurysm height (area under the curve [AUC] 0.60, P < 0.01) and aneurysm inclination angle (AUC 0.61, P = 0.02) in addition to a smaller dome (AUC 0.44, P = 0.02) and neck width (AUC 0.38, P < 0.01). Calculation of size ratios increases the predictive value for aneurysm rupture, with AUC values of 0.77 for aspect ratio (P < 0.01) and 0.76 for size ratio (P < 0.01). Aneurysm morphology was not a significant factor after multivariable adjustment (P = 0.20). Arterial hypertension was the only clinical risk factor significantly associated with rupture (P < 0.01). - Conclusions - Of the numerous factors associated with aneurysm rupture, we propose aneurysmal location, aspect ratio (cut-off: 1.5), and aneurysm inclination angle as the most important morphological factors for assessing the rupture risk of small aneurysms because these factors have high AUC values and are robust to changes after rupture.